The Effects of Learning Media and Motivation Towards Students' Reading Ability - Dody Wahyudi Purnama (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2022)
Dody Wahyudi Purnama, The Effects of Learning Media and Motivation toward the Students’ Reading Ability at Private Colleges in Subang Regency. The aim of the research is to know the effects of learning media and motivation towards students’ reading ability at private colleges in Subang regency. The total sample constitutes 50 students. The technique of collecting data used questionnaires and reading test by multiple choice with 20-item instrument. The methodology used is experiment research to know the effects of independent variables towards dependent variable. The statistic test used descriptive statistics and Tukey comparisons. The findings are 1). There is significant effects of learning media towards students’ reading ability at private collages in Subang regency, proved by the significance 0.000<0.05 and Fo = 102,914. The average of the students’ reading ability with high motivation is greater than that of with low motivation. The mean of the experiment class equals 81.42 and conventional class equals to 68.76. 2). There is effect of motivation towards students’ reading ability at private collages in Subang regency, and proved by the value of sig 0.000< 0.05. and Fo = 14,671. The total motivation is 77.48 for high motivation students, and 72.70 for low motivation students. 3) there is effect of learning media and motivation towards the students’ reading abilty, proved by the value of sig 0.005<0.05 and Fo=8,230.